2022
DOI: 10.1155/2022/2524832
|View full text |Cite
|
Sign up to set email alerts
|

Rhein Ameliorates Cognitive Impairment in an APP/PS1 Transgenic Mouse Model of Alzheimer’s Disease by Relieving Oxidative Stress through Activating the SIRT1/PGC-1α Pathway

Abstract: Mitochondrial oxidative stress plays an important role in the pathogenesis of Alzheimer’s disease (AD). Recently, antioxidant therapy has been considered an effective strategy for the treatment of AD. Our previous work discovered that rhein relieved mitochondrial oxidative stress in β-amyloid (Aβ) oligomer-induced primary neurons by improving the sirtuin 1 (SIRT1)/peroxisome proliferator-activated receptor gamma coactivator 1-alpha- (PGC-1α-) regulated mitochondrial biogenesis. While encouraging results have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…In this study, treatment with CH/PLA/MgONCs highly reduced the oxidative stress induced by ICV-STZ and restored the endogenous antioxidant defense system to normal levels. These findings are consistent with previous research demonstrating restoration of reduced endogenous antioxidant defense systems and highlighting the antioxidant activity of CH/PLA/MgONCs in justifying oxidative damage (Yin et al, 2022;Ali et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, treatment with CH/PLA/MgONCs highly reduced the oxidative stress induced by ICV-STZ and restored the endogenous antioxidant defense system to normal levels. These findings are consistent with previous research demonstrating restoration of reduced endogenous antioxidant defense systems and highlighting the antioxidant activity of CH/PLA/MgONCs in justifying oxidative damage (Yin et al, 2022;Ali et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, FPF reversed scopolamine-induced neuronal cell damage and reduced Nissl body counts, indicating its neuroprotective effects. This contributed to the amelioration of learning and memory function deficits. , …”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, sildenafil inhibited the expression of β-secretase 1 and the generation of Aβ via the CREB/PGC-1α and SIRT1/PGC-1α signaling pathways [ 309 ]. Rhein promoted mitochondrial biogenesis through upregulating protein expression of SIRT1 and its downstream PGC-1α and NRF1, thereby attenuating Aβ 1-42 oligomer-induced neuronal apoptosis [ 310 , 311 ]. In addition, Dezfouli et al observed increased protein expression of SIRT1 and TFAM, along with elevated mtDNA copy numbers, in the hippocampus of aβ-injected rats treated with melatonin for 14 consecutive days.…”
Section: Pharmacological Exploitation Of Sirtuins For Therapeutic Pur...mentioning
confidence: 99%